Impact of knowledge management on law firm performance - Forstenlechner, Ingo (Cranfield University, 2005)
It is a management truism that you cannot manage what you cannot measure. To manage knowledge effectively organisations need to understand how to measure their knowledge management performance against organisational goals. The case study organisation has developed a balanced scorecard, which is used to monitor key drivers for performance within the remit of the knowledge management function, thereby aiming to improve the delivery of value adding services. The set of cause and effect relationships at the heart of the scorecard - referred to as the success map - is at the core of this research, which aims to investigate if the link between managing knowledge and financial performance really exists and - if it does - how it can be influenced. By means of analytical methods including regression, correlation and semi-structured interviews the existence of this link is supported by evidence and the success map updated to reflect the relationships among key performance drivers that were positively identified as relevant. The outcome is a model for managing knowledge that can be applied to professional service firms or comparable organisations that are highly dependant on knowledge. In relation to this model, cultural variations were investigated and found to significantly influence the relevant performance drivers in several regions and countries across the case study organisation. Ignoring these cultural variations was found to carry the risk to base action on deceitful insights. In addition to this, the analysis of the survey also gave a clear indication of how to foster knowledge sharing among lawyers of different nationality and levels of seniority. This thesis provides the empirical evidence for a link between knowledge management and organisational performance.